2022
DOI: 10.1002/jso.27139
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes after synchronous para‐aortic lymph node metastasis in colorectal cancer: A systematic review

Abstract: Background: Synchronous para-aortic lymph node metastasis (PALNM) in colorectal cancer (CRC) is a relatively rare clinical entity. There is a lack of consensus on management of these patients, and the role of para-aortic lymph node dissection (PALND) remains controversial. This systematic review aims to describe the survival outcomes in colorectal cancer with synchronous PALNM when lymph node dissection is performed. Methods: A systematic review of Pubmed, Embase and Web of Science databases for PALND in CRC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…In general, surgeons are better trained in handling fresh specimens than pathologists and, thus, are more capable of meticulously retrieving lymph nodes from unfixed surgical specimens. Although this was not common practice for Western surgeons, we demonstrated that it achieved a satisfactory number of retrieved lymph nodes, up to a mean number of 34.4 per patient, which was higher than that reported previously 1 , 9 , 11 , 12 , 20 , 28 , 32 . Therefore, we believe that the large number of lymph nodes evaluated, and the methodology used to assess their anatomical location ensured the quality of lymph node mapping and subsequent survival correlation.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In general, surgeons are better trained in handling fresh specimens than pathologists and, thus, are more capable of meticulously retrieving lymph nodes from unfixed surgical specimens. Although this was not common practice for Western surgeons, we demonstrated that it achieved a satisfactory number of retrieved lymph nodes, up to a mean number of 34.4 per patient, which was higher than that reported previously 1 , 9 , 11 , 12 , 20 , 28 , 32 . Therefore, we believe that the large number of lymph nodes evaluated, and the methodology used to assess their anatomical location ensured the quality of lymph node mapping and subsequent survival correlation.…”
Section: Discussioncontrasting
confidence: 62%
“…However, excessive lymph node dissection can result in additional surgical complications, including profuse bleeding, prolonged ileus, intra-abdominal abscess formation, wound infection, anastomotic leakage, and permanent loss of sexual function. Given the lack of quality data to weigh the survival benefits against surgical morbidities, most researchers have suggested that D3-D4 lymph node dissection should be implemented with already established treatment regimens within a multidisciplinary approach for patients with advanced colorectal cancer 11 , 12 . Further prospective multicenter international studies with standardized definitions and surgical techniques are required to better evaluate the long-term oncological outcomes of D3-D4 lymph node dissection.…”
Section: Introductionmentioning
confidence: 99%